Entertainment in the Emirati Community: Religious and Social Dimensions During the Second Half of the Twentieth Century - Al-Ali, Mariam Ali Thani Alghawi; Idriz, Mesut (Al-Adab Journal, 2021)
The popular heritage is the main aspect of identity, besides; peoples' legacies are the basics on which the essence of human civilizations is based. The UAE was established in 1971, the history of the Emirates before its founding was not sufficient, especially in relation to the popular heritage of literature, arts, and games that represented the entertainment aspect of the Emirati society, we have only what has been memorized, what the generations have inherited that should be highlighted to demonstrate its nature, dimensions, and consequences. This will contribute, however, to opening a window to the past by researching those legacies and linking them to the transformation from the Pearl Diving Community to the United Arab Emirates. Recreation is one of the basics of life in the ancient and modern era. Human nature despite its variety shared many stable, indigenous needs as well as the close relationship between history and sciences that interacted to reflect a historical, social, humanitarian, and literature aspect of what man defines as civilization. Accordingly, the UAE community before the establishment of the Federation has enjoyed many kinds of entertainment, which has formed the main part of the UAE citizen's personality. Moreover, the society's knowledge of entertainment was not superficial as it is now due to technology, rather it was a philosophy of entertainment of different kinds that was derived from the nature of different environments in the UAE. Entertainment in UAE society was influenced by psychological, environmental, and political dimensions. The diver's trips contributed to attracting many aspects of entertainment that remained with the Emirati community even after the establishment of the union.